Rethinking training in elite soccer players: comparative evidence of small-sided games and official match play in kinematic parameters - Savoia, C.; Iellamo, F.; Caminiti, G.; Doran, D. A.; Pullinger, S.; Innaurato, M. R.; Annino, G.; Manzi, V. (The Journal of Sports Medicine and Physical Fitness, 2021)
BACKGROUND: The aim of this study was to compare kinematics parameters among official matches and SSGs of an Italian premier league soccer team. METHODS: Eighteen elite professional male soccer players (4 central defenders, 4 wide defenders, 3 central midfielders, 3 box-to-box midfielders, 2 wingers and 2 strikers) took part in the study. Players were monitored during four months of full training (including preseason and in-season) and over 26 matches (14 Serie A matches, 9 Europa League matches, and 3 friendly matches), from July 2017 until November 2017. The kinematic parameters during official matches and SSGs were evaluated through video match analysis. RESULTS: The kinematic data analysis shows that the metabolic power, that constitutes an integrated measure of acceleration and velocity, fails to reflect what occurs during actual match-play. CONCLUSIONS: An increased attention should be place in planning SSGs during training to better reproduce actual match situations.